Role of lifestyle and oral anti-diabetic agents to prevent type 2 diabetes mellitus and cardiovascular disease. - Bethel, M; Califf, R (2007)
Patients with type 2 diabetes mellitus (DM) and those with impaired glucose tolerance are at increased risk for the development of cardiovascular disease. With an increasing global incidence and prevalence of type 2 DM, and with the 2003 lowering of the glucose threshold required for the diagnosis of impaired glucose tolerance to 100 mg/dl (5.6 mmol/L), the concept of DM prevention, and presumed reduction of cardiovascular risk, is attractive. However, there is little evidence to guide the choice of DM prevention strategy and no certainty that DM prevention will result in reduced cardiovascular events or an overall favorable balance of benefit to risk. In conclusion, this review examines previous reports on DM prevention, with special attention to evidence for cardiovascular event reduction in association with specific interventions to prevent DM.